2010
DOI: 10.1038/onc.2010.209
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the receptor tyrosine kinase RET sensitizes breast cancer cells to tamoxifen treatment and reveals a role for RET in endocrine resistance

Abstract: Endocrine therapy is the main therapeutic option for patients with estrogen receptor (ERa)-positive breast cancer. Resistance to this treatment is often associated with estrogen-independent activation of ERa. In this study, we show that in ERa-positive breast cancer cells, activation of the receptor tyrosine kinase RET (REarranged during Transfection) by its ligand GDNF results in increased ERa phosphorylation on Ser118 and Ser167 and estrogen-independent activation of ERa transcriptional activity. Further, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(154 citation statements)
references
References 53 publications
8
145
1
Order By: Relevance
“…Immunohistochemical analysis of the BCCA TMA samples has demonstrated broad expression across all breast cancer subtypes, with the highest prevalence in HER2 þ and basal breast cancers. This is in contrast to previous studies that reported preferential expression of RET in ER þ breast cancer but with relatively little expression in HER2 þ and basal breast cancers (17,18,29,30). The explanation for the discordance is not clear; however, it may reflect differences in the methods (in situ hybridization vs. immunohistochemistry), protocols, reagents, sample set sizes, or patient treatment history.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Immunohistochemical analysis of the BCCA TMA samples has demonstrated broad expression across all breast cancer subtypes, with the highest prevalence in HER2 þ and basal breast cancers. This is in contrast to previous studies that reported preferential expression of RET in ER þ breast cancer but with relatively little expression in HER2 þ and basal breast cancers (17,18,29,30). The explanation for the discordance is not clear; however, it may reflect differences in the methods (in situ hybridization vs. immunohistochemistry), protocols, reagents, sample set sizes, or patient treatment history.…”
Section: Discussioncontrasting
confidence: 54%
“…Increased RET expression has been associated with decreased metastasis-free survival (HR, 2.12; P ¼ 0.0476) and overall survival (HR, 1.95; P ¼ 0.0438) in patients with breast cancer (15), and RET inhibition decreased growth and metastasis of ER þ breast cancer cells (15,16). Increased expression of RET has also been observed in primary tumors from patients who have failed tamoxifen therapy, suggesting a role for RET in endocrine resistance (17). Although the mechanism of this resistance is not well understood, RET expression is upregulated in response to estrogen treatment, and RET activation by GDNF results in increased ERa phosphorylation and activation of known ERa target genes (18).…”
Section: Introductionmentioning
confidence: 89%
“…ERα is a member of the steroid receptor superfamily and regulates growth, differentiation and other processes in various target cells by regulating transcriptional processes (19). It is also important in the development and progression of breast cancer (20) and is expressed in ~70% of breast cancers (21), which makes it difficult to obtain a response to cancer drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was demonstrated between RET over-expression and estrogen receptor-positive breast carcinoma [41,42]. Importantly, RET inhibition restored a hormone-sensitive phenotype in anti-estrogen resistant breast cancer cells [43]. Furthermore, RET protein was overexpressed in pancreatic carcinoma and involved in neural invasion of pancreatic cancer cells [44,45].…”
Section: Ret Over-expression In Cancermentioning
confidence: 82%